1975
DOI: 10.1007/bf00350636
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between temperature and duration of egg development in some epiphytic cladocera and copepoda from the River Thames, reading, with a discussion of temperature functions

Abstract: Data on the duration of egg development at 5, 10, 15 and 20°C are given for eight cladoceran and one cyclopoid copepod species found associated with the Yellow Water Lily (Nuphar lutea) in the River Thames. A decrease in temperature caused a marked increase in the time taken to complete development for all nine species. The data are compared with published data and a number of conclusions drawn. In general, cladoceran eggs tend to take longer to complete development than copepod eggs, and within the Cladocera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
84
2
4

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 32 publications
14
84
2
4
Order By: Relevance
“…0, 6.6, 8.4) and on all versions of food (algae Chlamydomonas reinhardi, detritus and filtered pond water containing only microorganisms < 30 µm). This is consistent to other studies that found similar egg development times of C. sphaericus (Bottrell, 1974;Meyers, 1984). The universal presence of this species is also provided by its population ability to grow at a faster rate than the other species when fed on an algal culture and on filtered pond water, suggesting that in addition to using algal mats as a substratum on which to live (Fryer, 1968;Havens, 1991), it is also able to feed on bacteria and tiny detritus particles (< 30 µm) (Fryer, 1968).…”
Section: > Chydorus Sphaericussupporting
confidence: 91%
“…0, 6.6, 8.4) and on all versions of food (algae Chlamydomonas reinhardi, detritus and filtered pond water containing only microorganisms < 30 µm). This is consistent to other studies that found similar egg development times of C. sphaericus (Bottrell, 1974;Meyers, 1984). The universal presence of this species is also provided by its population ability to grow at a faster rate than the other species when fed on an algal culture and on filtered pond water, suggesting that in addition to using algal mats as a substratum on which to live (Fryer, 1968;Havens, 1991), it is also able to feed on bacteria and tiny detritus particles (< 30 µm) (Fryer, 1968).…”
Section: > Chydorus Sphaericussupporting
confidence: 91%
“…The effect of temperature on the egg development time of various cladocerans in the laboratory has been reported by many authors (HALL, 1964;BOTTRELL, 1975;KERFOOT, 1975;KWIK and CARTER, 19/5;MUNRO and WHITE, 1975;ALLAN, 1977;VIIVERBERG, 1980). However, there are very few studies on Moina micrura and Bosmina f atalis.…”
mentioning
confidence: 67%
“…To relate the duration of egg development and age at first parturition to temperature, the following regression equation of BoTTRELL (1975) was used,…”
Section: Methodsmentioning
confidence: 99%
“…An approximate sequence of embryonic stages was superficially described only for a single chydorid species, Leydigia acanthocercoides (Leydig, 1860) (Murugan and Job, 1982) and for the closest relative of (Kotov, 1996) Bottrell (1975aBottrell ( , 1975b, Melão (1997Melão ( , 1999 and their own observations. From our data, we can say that the general patterns of the sequence of events in chydorid embryogenesis is similar to that in other anomopods, such as the daphniids Daphnia magna (Obreshkove and Frazer, 1940), D. hyalina and D. galeata (Kotov and Boikova, 2001), and Ceriodaphnia reticulata (Shuba and De Costa, 1972).…”
Section: Discussionmentioning
confidence: 99%